Antisense Tissue Factor Oligodeoxynucleotides Protected Diethyl Nitrosamine/Carbon Tetrachloride-Induced Liver Fibrosis Through Toll Like Receptor4-Tissue Factor-Protease Activated Receptor1 Pathway - Shouman, Maha M.; Abdelsalam, Rania M.; Tawfick, Mahmoud M.; Kenawy, Sanaa A.; El-Naa, Mona M. (Frontiers in Pharmacology, 2021)
Tissue factor (TF) is a blood coagulation factor that has several roles in many non-coagulant pathways involved in different pathological conditions such as angiogenesis, inflammation and fibrogenesis. Coagulation and inflammation are crosslinked with liver fibrosis where protease-activated receptors1 (PAR1) and toll-like receptor4 (TLR4) play a key role. Antisense oligodeoxynucleotides are strong modulators of gene expression. In the present study, antisense TF oligodeoxynucleotides (TFAS) was evaluated in treating liver fibrosis via suppression of TF gene expression. Liver fibrosis was induced in rats by a single administration of N-diethyl nitrosamine (DEN, 200 mg/kg; i.p.) followed by carbon tetrachloride (CCl4, 3 ml/kg; s.c.) once weekly for six weeks. Following fibrosis induction, liver TF expression was significantly upregulated along with liver enzymes activities and liver histopathological deterioration. Alpha smooth muscle actin (α-SMA) and transforming growth factor-1beta (TGF-1β) expression, tumor necrosis factor-alpha (TNF-α) and hydroxyproline content and collagen deposition were significantly elevated in the liver. Blocking of TF expression by TFAS injection (2.8 mg/kg; s.c.) once weekly for six weeks significantly restored liver enzymes activities and improved histopathological features along with decreasing the elevated α-SMA, TGF-1β, TNF-α, hydroxyproline and collagen. Moreover, TFAS decreased the expression of both PAR1 and TLR4 that were induced by liver fibrosis. In conclusion, we reported that blockage of TF expression by TFAS improved inflammatory and fibrotic changes associated with CCl4+DEN intoxication. In addition, we explored the potential crosslink between the TF, PAR1 and TLR4 in liver fibrogenesis. These findings offer a platform on which recovery from liver fibrosis could be mediated through targeting TF expression.